Acute pancreatitis and serological evidence of infection with Mycoplasma pneumoniae. Issue 5 (May 1978) - Freeman, R; McMahon, M J
Abstract : Paired acute and convalescent serum samples from 27 consecutive patients with acute pancreatitis were examined for evidence of infection with several viral agents. Evidence of infection with Coxsackie viruses group B was found in three patients, and of infection with Mycoplasma pneumoniae in nine patients (33%). This latter finding confirms recent reports from Scandinavia linking pancreatitis and serological evidence of infection with Mycoplasma pneumoniae. The possibility that a true association exists between the two conditions is considered, together with alternative explanations, and further work is envisaged to elucidate these findings.